Targeting histone deacetylases for cancer therapy: Trends and challenges - Tao Liang; Fengli Wang; Reham M. Elhassan; Yongmei Cheng; Xiaolei Tang; Wengang Chen; Hao Fang; Xuben Hou (Elsevier, 2023)
Dysregulation of histone deacetylases (HDACs) is closely related to tumor development and progression. As promising anticancer targets, HDACs have gained a great deal of research interests and two decades of effort has led to the approval of five HDAC inhibitors (HDACis). However, currently traditional HDACis, although effective in approved indications, exhibit severe off-target toxicities and low sensitivities against solid tumors, which have urged the development of next-generation of HDACi. This review investigates the biological functions of HDACs, the roles of HDACs in oncogenesis, the structural features of different HDAC isoforms, isoform-selective inhibitors, combination therapies, multitarget agents and HDAC PROTACs. We hope these data could inspire readers with new ideas to develop novel HDACi with good isoform selectivity, efficient anticancer effect, attenuated adverse effect and reduced drug resistance.